Fighting Polio: Why Radio Dramas Failed in Pakistan? - Ullah Khan, Altaf; Jan, Faizullah; Fawad Ali Shah, Sayyed (The Journal of Humanities & Social Sciences, 2023)
Entertainment Education strategies have been successfully used in health campaigns for the prevention of different diseases across the globe, especially in the under-developed countries. Radio drama is an important instrument of the Entertainment Education strategies. Radio dramas have been used in successful health campaigns in Africa and Asia. Radio dramas have been particularly successful in targeting the underprivileged population. Deutsche Welle (DW), the German international broadcaster, keeping in mind the effectiveness of radio dramas in bringing social change, introduced this genre of drama in Pakistan in 2012. The radio station produced and aired radio dramas targeting Pakhtoon population that resides in Northwestern province of Pakistan. The Pakhtoon population traditionally lives in the tribal setup; they lag in terms of socio- economic and political development. These dramas were aimed at creating awareness about health and bringing positive changes in social behavior and general well-being of the targeted population. This paper presents a discourse analysis of radio dramas. The study attempts to determine whether the dramas’ scripts adhere to any theoretical framework of the EE or health campaigns strategies? Other questions addressed by the authors include: What messages were included in the radio broadcasts analyzed? Was the production process based on any theoretical foundation? What themes were developed in the radio broadcasts analyzed? What types of characters were featured in the broadcasts? It is argued that the production process was not based on any theoretical framework. The dramas did not adhere to the basic principles of the Education Entertainment strategies and health communication campaigns.